Impact of Socioeconomic Characteristics and Productivity on Output of Okra Farmers in Ikwerre Local Government Area, Rivers State, Nigeria - Amadi Robert C.C (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study investigates the impact of socioeconomic characteristics and productivity on output of Okra farmers in Ikwerre Local Government Area, Rivers State. The objectives of this study were to examine the socio-economic characteristics of the respondents in the study area, investigate how productivity improve the output of okra farmers in the study area, and identify the problems associated with Okra production in Ikwerre Local government area of Rivers state and examine how profitability of Okra farmers enhance production of small-scale farmers in Ikwerre LGA. The population of the study is 2989 registered okra farmers in Ikwerre Local Government Area. Data were collected from 149 respondents drawn from the study area using multi-stage sampling stage techniques.Data were analyzed using descriptive statistics such as frequencies, percentages, mean scores (four-point Likert scale), stochastic frontier production function, Gross margin and multiple regressions. The results from the analysis (gross margin) revealed that the total variable cost at N8, 530.130 and total revenue at N11, 520,000 gave a gross margin of N2, 989,870 and a rate of return of N1.35k. this implies that, Okra farming is profitable in the study area